2006
DOI: 10.1056/nejmoa055218
|View full text |Cite|
|
Sign up to set email alerts
|

Calcium plus Vitamin D Supplementation and the Risk of Fractures

Abstract: Among healthy postmenopausal women, calcium with vitamin D supplementation resulted in a small but significant improvement in hip bone density, did not significantly reduce hip fracture, and increased the risk of kidney stones. (ClinicalTrials.gov number, NCT00000611.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
918
5
39

Year Published

2006
2006
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,649 publications
(1,000 citation statements)
references
References 33 publications
22
918
5
39
Order By: Relevance
“…On the other hand, the beneficial effect of combined calcium and vitamin D supplementation for fracture prevention in the frail elderly population is considered as documented and constitutes a recommended intervention against bone loss (Kannus et al, 2005). Nevertheless, results from randomized controlled trials concerning the antifracture efficacy of calcium and/or vitamin D intake are not in agreement (Jackson et al, 2006;Bischoff-Ferrari et al, 2007;Tang et al, 2007). In this population of elderly Europeans, no association between hip fracture risk and consumption of dairy products or intake of calcium or vitamin D was observed.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the beneficial effect of combined calcium and vitamin D supplementation for fracture prevention in the frail elderly population is considered as documented and constitutes a recommended intervention against bone loss (Kannus et al, 2005). Nevertheless, results from randomized controlled trials concerning the antifracture efficacy of calcium and/or vitamin D intake are not in agreement (Jackson et al, 2006;Bischoff-Ferrari et al, 2007;Tang et al, 2007). In this population of elderly Europeans, no association between hip fracture risk and consumption of dairy products or intake of calcium or vitamin D was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The 2007 meta-analysis also included the Women's Health Initiative (WHI) study [20], a large randomized controlled trial with a 7-year follow-up, which showed a nonsignificant decrease in hip fractures (RR = 12%). However, when the study was analyzed to exclude nonadherent subjects (those who took vitamin D and calcium < 80% of the time), calcium and vitamin D intake decreased the relative risk of hip fractures by 29%, which was statistically significant.…”
Section: Skeletal Benefits Of Calcium and Vitamin Dmentioning
confidence: 99%
“…While widely recommended, calcium has been shown to be necessary but not sufficient for reducing osteoporosis risk. 17 A previous randomized controlled trial in healthy older women with prespecified CVD outcomes showed possible increases in MI and cardiovascular events in women who took calcium. 18 What this Study Adds This meta-analysis included 15 RCTs that had at least 100 participants aged 40 and older and had a study duration of at least 1 year.…”
Section: What This Study Addsmentioning
confidence: 99%